PENGARUH PENGUKUSAN DAN PERAJANGAN DAUN GAMBIR (Uncaria gambir ROXB) TERHADAP MUTU EKSTRAK GAMBIR - Zulnely Zulnely; Abdul Hakim Lukman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
This experiment is 10 study the effect of steaming duration and chopping sizes of gambier leaves (Uncaria gambir ROXB) on both yield and quality.The steaming duration of the samples were conducted at 30,40, 60 and 75 minutes and tire chopping sizes of tire sample consisted of 0.5-1 cm, 2-3 cm, 4-6 cm, and unchopping, The results were analyzed using the factorial design with two replicates and the difference between means were tested with multiple range Duncan